Pengaruh Lingkungan Kerja dan Komunikasi Terhadap Kepuasan Kerja pada Tunas Toyota Tangerang: The Influence of the Work Environment and Communication on Job Satisfaction at Tunas Toyota Tangerang - Salma Julia Putri Suryadi; Susanti Susanti (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to examine the effect of work environment and communication on employee job satisfaction at Tunas Toyota Tangerang, both partially and simultaneously. The study is motivated by several work environment conditions that still require improvement and internal communication issues that may affect employee job satisfaction. A quantitative approach was employed with a population of 57 employees and a sample of 51 respondents selected through purposive sampling. Primary data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics 25. The results show that work environment has a positive and significant effect on job satisfaction (t count 3.324 > t table 2.011; sig. 0.002), communication has a positive and significant effect and is the most dominant variable (t count 9.085 > t table 2.011; sig. 0.000), and work environment and communication simultaneously have a positive and significant effect on job satisfaction (F count 162.574 > F table 3.191; sig. 0.000), contributing 87.1%. These findings indicate that improving workplace conditions and organizational communication effectiveness together can enhance employee job satisfaction.